Managers as entrepreneurs a view from Asia - Minkes, A.L (Technovation)
This paper reproduces a 'keynote' address [1] given by the author at a conference held in Hong Kong in May 1994. The conference, organized by the Management Development Centre of Hong Kong and the Hong Kong Productivity Council, was attended by some 380 participants from 23 countries. The paper is concerned with the demands made on managers in modern business organizations. It suggests that innovative entrepreneurial behaviour and responsibility may be required in varying degrees at all levels of an organization, particularly in the complex international environment in which business has to operate. This is true for Asian business as it is for business generally. At the same time, however, there has to be regard to the special cultural context of Asian countries which governs the ways in which management ability can be developed. Many of the ideas about management development have their origin in Western thought and conditions and, even there, substantial differences may exist between individual countries-for example, in attitudes towards hierarchy. Thus, a pluralist approach to management development is required which takes account both of common insights and of cultural diversity.